Update on treatment of immunoglobulin A nephropathy. (8th October 2018) - Zhang, Yue‐Miao; Zhang, Hong
ABSTRACT: Immunoglobulin A nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide and the most common cause of end‐stage renal disease in young adults. However, there are still no specific therapies capable of targeting key pathways involved in disease pathogenesis. Recently, many large randomized controlled trials have been reported, such as Supportive Versus Immunosuppressive Therapy for the Treatment of Progressive IgA Nephropathy, Targeted‐release Budesonide Versus Placebo in Patients with IgA Nephropathy and Therapeutic Evaluation of Steroids in IgA Nephropathy Global, which are considered to update the 2012 Kidney Disease: Improving Global Outcomes Guideline. More importantly, with a deeper understanding of the roles of mucosal immunity, B‐cell activation and complement activation in IgAN, the studies of targeting pathogenic pathways are ongoing. In this review, by systemically searching the clinical trials in IgAN onClinicalTrials.gov (https://clinicaltrials.gov/ ), we update the evidence for corticosteroids/immunosuppressive therapy in IgAN and explore the promising targeting pathogenic pathway therapeutic options. With better understanding of pathogenesis of IgAN, emerging therapies will soon become a reality in future. Summary at a Glance: By systemically searching the clinical trials in immuglobulin A nephropathy, we update the available treatments and explore the promising targeting pathogenic pathway therapeutic options.